An Approach of Historical and Economic BRICS Creation in South-South Cooperation Resurgence Landmark in the Twenty-First Century - Galdino, Gabriel (Conjuntura internacional, 2021)
In the history of international relations, the association between developing countries occurred on a reduced scale until the mid-twentieth century. This article takes a historical and economic approach about the formation of the movements characterized as South-South Cooperation, including the emergence of the BRICS in the 21st century.